Exposure, access, and inequities: Central themes, emerging trends, and key gaps in Canadian environmental justice literature from 2006 to 2017. (8th March 2022) - Giang, Amanda; Boyd, David R.; Ono, Aspen J.; McIlroy‐Young, Bronwyn
Abstract : Environmental injustices—in the form of inequitable distribution of environmental risks and benefits, uneven access to decision‐making processes, and misrecognition of communities—have been documented globally. However, in Canada, many have argued that the story of environmental injustice is less widely known, with more fragmented research that has produced little in terms of public policies intended to alleviate injustice. This paper uses a meta‐narrative review approach to map the evolution of environmental justice research in Canada between 2006‐2017, and characterize how central themes, emerging trends, and gaps in the literature have changed since the last review of this kind was completed. We conducted a systematic search of publications addressing environmental justice in Canada, yielding 820 publications. We coded abstracts to assess patterns of coverage across space, time, topics, and populations of focus. We find that Canadian environmental justice literature has continued to grow in quantity and scope, addressing more dimensions of environmental harms and benefits, and from an increasingly integrated perspective. However, there remain important and persistent gaps in its coverage. Future research that more fully addresses these geographic (e.g., Atlantic and Prairie regions), topical (e.g., focus on prevention), and recognitional (e.g., racialization) gaps is needed to inform policy‐making and promote justice . Key Messages: Using a meta‐narrative review approach, we characterize the evolution of environmental justice research in Canada from 2006 to 2017, and draw comparisons to an earlier review. We find increased attention to multi‐sited investigations, access to environmental benefits, climate change, drinking water systems, and an intersectional approach to social vulnerability, particularly for Indigenous communities. Persistent gaps in the literature include understudied geographic regions, recognitional dimensions (e.g., racialization as a form of social stratification), and a focus on prevention and promoting justice. Exposition, accès et iniquités : Thèmes centraux, nouvelles tendances et principales lacunes dans les travaux sur la justice environnementale canadienne de 2006 à 2017: Les injustices environnementales sous diverses formes ont été largement documentées dans le monde universitaire. Toutefois, au Canada, plusieurs ont fait valoir que le domaine de l'injustice environnementale est moins bien connu, compte tenu de recherches plus fragmentées et peu influentes sur le plan des politiques publiques. Cet article utilise une approche d'examen métanarratif pour illustrer l'évolution des recherches sur la justice environnementale au Canada, entre 2006 et 2017. Plus précisément, il s'agit de caractériser la façon dont les thèmes centraux, les nouvelles tendances et les lacunes de la documentation ont changé depuis que le dernier examen de ce genre a été réalisé. Nous avons donc effectué une recherche documentaire systématique sur la justice environnementale au Canada, celle‐ci générant 820 publications. Nous avons ensuite codé les résumés pour évaluer les types de couverture en fonction de l'espace, du temps, des thèmes et des populations visées. Nous concluons que la documentation sur la justice environnementale canadienne a continué de croître en quantité et en étendue. Toutefois, il reste des lacunes importantes et persistantes dans le traitement des sujets. À notre avis, les recherches à venir devraient aborder de manière plus complète ces lacunes géographiques (p. ex., les régions de l'Atlantique et des Prairies), thématiques (p. ex., l'accent sur la prévention) et de reconnaissance (p. ex., la racisation) .